VD_FINDINFO Décision / 2013 / 854 vom 15. Oktober 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ, SOUPÇON | 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 222 CPP (CH)